The effects of probiotics plus dietary fiber on antipsychotic-induced weight gain: a randomized clinical trial - Jing Huang (Translational Psychiatry, 2022)
Abstract Probiotics plus dietary fiber has demonstrated efficacy in improving metabolic abnormalities. However, the efficacy of probiotics and dietary fiber as well as their association with microbiota in attenuating antipsychotic-induced weight gain and metabolic disturbance remains poorly understood. Here we analyzed results from the double-blind, randomized, placebo-controlled study to compare and evaluate the effects of probiotics, dietary fiber, and their combination for antipsychotic-induced weight gain in patients with a severe mental disorder. We found that probiotics plus dietary fiber was significantly superior to probiotics alone, dietary fiber only, and the placebo for weight, BMI, and total cholesterol reduction; insulin resistance was worse in the placebo group, with significant increases during the 12-week treatment; probiotics plus dietary fiber significantly reduced weight and prevented further deterioration of metabolic disturbances; and probiotics or dietary fiber alone can prevent further weight gain. We further performed 16 S ribosomal RNA sequencing revealed an increased abundance of microbiota after probiotics plus dietary fiber treatment. Moreover, logistic regression analyses revealed that the higher richness of microbiota was associated with favorable weight loss. These findings suggested that probiotics and dietary fiber co-administration were safe and effective interventions to reduce weight gain in patients treated with antipsychotic medications.